Dynamic evolution of size and colour in the highly specialized Zodarion ant-eating spiders - Ortiz, David; Pekár, Stano; Bilat, Julia; Shafaie, Sepideh; Alvarez, Nadir; Gauthier, Jérémy (Proceedings. Biological sciences, 2023)
Ecological specialists constitute relevant case studies for understanding the mechanisms, potential and limitations of evolution. The species-rich and strictly myrmecophagous spiders of the genus Zodarion show diversified defence mechanisms, including myrmecomorphy of different ant species and nocturnality. Through Hybridization Capture Using RAD Probes (hyRAD), a phylogenomic technique designed for sequencing poorly preserved specimens, we reconstructed a phylogeny of Zodarion using 52 (approx. a third of the nominal) species that cover its phylogenetic and distributional diversity. We then estimated the evolution of body size and colour, traits that have diversified noticeably and are linked to defence mechanisms, across the group. Our genomic matrix of 300 loci led to a well-supported phylogenetic hypothesis that uncovered two main clades inside Zodarion. Ancestral state estimation revealed the highly dynamic evolution of body size and colour across the group, with multiple transitions and convergences in both traits, which we propose is likely indicative of multiple transitions in ant specialization across the genus. Our study will allow the informed targeted selection of Zodarion taxa of special interest for research into the group's remarkable adaptations to ant specialization. It also exemplifies the utility of hyRAD for phylogenetic studies using museum material.
Keywords: predátorské chování; phylogenomics; pavouci; Color; prey shift; genomika; Predatory Behavior; Animals; mimicry; morphological evolution; Genomics; Phylogeny; museomics; zvířata; fylogeneze; Spiders; barva; hyRAD sequencing